Use the substitution u=1+e^x to find the Integral of e^(3x) / (1 + e^x)

ex=u-1 so e3x=(u-1)3 and du/dx = ex so rearranging gives dx=e-x du Substituting all that information in the integral we get Integral ( (u-1)3/ (u(u-1)) du ) which simplifies to Integral (u -2 +1/u).Integrating we get u2/2 -2u + ln u + C and substituting the original variable we get (1+ex)2/2 -2(1+ex) + ln (1+ex) + C

Answered by Ismet P. Maths tutor

9713 Views

See similar Maths A Level tutors

Related Maths A Level answers

All answers ▸

Solve x^3+2x^2+x=0


What is product rule differentiation?


a) Integrate ln(x) + 1/x - x to find the equation for Curve A b) find the x coordinate on Curve A when y = 0.


integrate (2x)/(x^2+1) dx with limits 1, 0


We're here to help

contact us iconContact usWhatsapp logoMessage us on Whatsapptelephone icon+44 (0) 203 773 6020
Facebook logoInstagram logoLinkedIn logo
Cookie Preferences